Impact of Game-Based Physical Education on Health Literacy and Physical Fitness in Primary School Children: A Scoping Review - Harahap, Andes Martua; Febriansyah, Wahyu (CV. INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This scoping review examined the impact of game-based physical education (PE) interventions on health literacy and physical fitness outcomes in primary school children (6-12 years). The objective was to synthesize existing literature, identify research gaps, and provide recommendations for evidence-based practice. Materials and methods: A comprehensive systematic literature review following PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines was conducted. Electronic databases including MEDLINE (PubMed), ERIC, Web of Science, SPORTDiscus, Scopus, and EBSCO were searched from January 2015 to October 2024. Peer-reviewed studies in English examining game-based PE interventions with primary school populations were included. Data extraction captured study design, population characteristics, intervention components, and outcome measures related to health literacy, physical fitness, and psychological well-being. Results: The initial search yielded 706 articles; 37 studies met inclusion criteria. Game-based PE interventions demonstrated significant improvements in moderate-to-vigorous physical activity (MVPA: standardized mean difference [SMD] 0.15, 95% CI 0.01–0.29), physical fitness parameters (including VO₂max, body composition, and fundamental motor skills), and health literacy knowledge. Motivational engagement and adherence rates were notably higher in gamified interventions compared to traditional PE approaches. Achievement-based game elements with embedded feedback were the most effective intervention components. Conclusions: Game-based PE represents a promising pedagogical approach to simultaneously enhance physical fitness and health literacy in primary school children. The integration of game mechanics into PE curricula fosters intrinsic motivation, improves physical competence, and supports the development of health-related knowledge and behaviors. However, heterogeneity in intervention design, outcome measurement, and population characteristics necessitates further high-quality randomized controlled trials to establish definitively the optimal implementation strategies for sustainable health promotion in school settings.